2016
DOI: 10.1016/j.jnucmat.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Lattice expansion by intrinsic defects in uranium by molecular dynamics simulation

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Our solute-vacancy and divacancy binding energies thus suggest that nucleation and growth of fission gas bubbles are supported by a thermodynamic driving force which is absent for void formation from joining of vacancies. This is in agreement with Li et al, who have reported that, at high temperatures, bcc uranium softens and swells mainly by agglomeration of noble gas bubbles [74].…”
Section: Solute-vacancy Defect Pairs In Bcc Uraniumsupporting
confidence: 93%
“…Our solute-vacancy and divacancy binding energies thus suggest that nucleation and growth of fission gas bubbles are supported by a thermodynamic driving force which is absent for void formation from joining of vacancies. This is in agreement with Li et al, who have reported that, at high temperatures, bcc uranium softens and swells mainly by agglomeration of noble gas bubbles [74].…”
Section: Solute-vacancy Defect Pairs In Bcc Uraniumsupporting
confidence: 93%
“…The low interstitial formation energy is also predicted in bcc titanium (that is unstable at low temperatures as bcc U) [20]. However, E int f is higher than E vac f at zero temperature in the COMB model [21] (which predicts the elastic properties quite well [21,22]).…”
Section: Introductionmentioning
confidence: 68%